Estudo molecular de antígenos eritrocitários em doadores de sangue e pacientes com doenças hematológicas : aplicação em medicina transfusional - Cruz, Bruno Ribeiro [UNIFESP] (2017)
Background: Programs to prevent alloimmunization against red blood cells antigens aims to provide antigen-compatible blood transfusions for patients with hematological diseases. Recently, there is an emerging role of molecular methods in donor-receptor compatibility for major blood group polymorphisms and for Rh variants to improve transfusion therapy. Aims: To determine the genotype and allele frequencies of major blood group systems and RHD and RHCE variants in blood donors, SCD patients, patients with Myelodysplastic Syndromes (MDS), Acute Myeloid Leukemia (AML) and Autoimmune Hemolytic Anemia (AIHA) through molecular analyses, to verify if the genotyping results are in concordance with serologic typing results and to perform molecular compatibility aiming to select compatible blood donors for these patients. Methods: Samples from 198 blood donors were phenotyped for five clinically relevant blood-group system antigens. Samples from 158 patients with hematological diseases (101 with SCD, 14 with MDS, 26 with AIHA and 17 with AML) and from 198 blood donors were evaluated molecularly for alleles from 18 blood-group systems using the blood-MLPA assay (Multiplex Ligation-dependent Probe Amplification) and gene sequencing. Results: We found statistically significant differences in the frequencies of the blood group alleles MNS, FY, JK, DO, CO, GE and RH (RHD*DAU0, RHCE*ceVS.01, RHCE*Ce and RHCE*CE) between the donor and patients with hematological diseases groups. Eight donors and nine patients had clinically relevant RHD genotypes. Thirteen donors and 22 patients had clinically relevant RHCE genotypes. There was 99,2% of concordance between the results of the serologic typing and the results of the predicted phenotypes by the blood-MLPA. The results indicate that it would be possible to find compatible blood donors for 91,1% of patients with hematological diseases. From recently transfused patients, 70,3% would have enough blood units for an annual transfusion cycle. The number of compatible donors was not sufficient to fulfil the transfusion needs of patients with Rh variants. Conclusion: We reliably determine the genotype and allele frequencies of clinically relevant blood-group systems in donors and in patients using molecular methods. The genotyping results were in agreement with phenotyping results. It would be possible to meet the transfusion needs of most patients with hematological diseases through molecular compatibility, but the current donor population would not fill the transfusion requirements of patients with Rh variants. Molecular compatibility increases the safety of patients with SCD, MDS, AML and AIHA by providing more accurate compatibility with genotyped donors and by reducing the risk of transfusion reactions.